The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.17221/84/2015-cjas
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression and tissue distribution of β-defensins in Chinese Min pigs and Landrace pigs

Abstract: Jiao W., Ma Q., Lv X., Shan A., Li Z. (2017): Gene expression and tissue distribution of β-defensins in Chinese Min pigs and Landrace pigs. Czech J. Anim. Sci., 62,[178][179][180][181][182][183] β-Defensins are a major group of mammalian antimicrobial peptides and play an important role in innate and adaptive immunity due to their antimicrobial, chemotactic, and regulatory activities. In this study, the tissue distribution of porcine β-defensin (pBD-1, pBD-2, and pBD-3) gene expression was determined using rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Our experimental results have shown that the transcriptional abundance of GHRL, LEP and their receptor genes, as well as SST and CCK, was influenced by age and tissue type, and the expression levels varied considerably between TP and YP. Previous research on β-defensins and Toll-like receptors 1-10 revealed similar expression patterns in different tissues of pigs (Qi et al 2009;Uddin et al 2013;Jiao et al 2017).…”
Section: Discussionmentioning
confidence: 79%
“…Our experimental results have shown that the transcriptional abundance of GHRL, LEP and their receptor genes, as well as SST and CCK, was influenced by age and tissue type, and the expression levels varied considerably between TP and YP. Previous research on β-defensins and Toll-like receptors 1-10 revealed similar expression patterns in different tissues of pigs (Qi et al 2009;Uddin et al 2013;Jiao et al 2017).…”
Section: Discussionmentioning
confidence: 79%
“…coli , and Bacillus subtilis and relieve intestinal inflammation and diarrhea in pigs (Holani et al, 2016 ). β-defensin plays an essential role in innate and adaptive immunity of vertebrates and has inhibitory effects against pathogenic bacteria, fungi, mycobacteria, and enveloped viruses (Auvynet and Rosenstein, 2009 ; Jiao et al, 2017 ). Pigs fed with fodder supplemented with a specific amino acid and cation mixtures showed the increase in expression of β-defensin genes.…”
Section: Treatment and Preventive Strategies To Combat Antibiotic Res...mentioning
confidence: 99%
“…In vertebrate animals, defensins are classified into three sub-groups, namely α-defensins, β-defensins, and θ-defensins, based on distribution of cysteine residue that forms the disulfide bridges and the length ( 27 ). Defensins produced by cells in the course of innate immune response serve as signals that initiate, mobilize, and amplify adaptive immune host defenses ( 28 ). β-defensins are known to play an essential role in innate and adaptive immunity due to their antimicrobial, chemotactic, and regulatory activities ( 28 ).…”
Section: Endogenous Antimicrobial Peptides That Enhance Porcine Healthmentioning
confidence: 99%
“…Defensins produced by cells in the course of innate immune response serve as signals that initiate, mobilize, and amplify adaptive immune host defenses ( 28 ). β-defensins are known to play an essential role in innate and adaptive immunity due to their antimicrobial, chemotactic, and regulatory activities ( 28 ). β- defensins exert inhibitory effects on pathogenic bacteria, fungi, mycobacteria, and enveloped viruses , particularly by creating pores on the microbial membrane surface to increase cellular permeability ( 29 ).…”
Section: Endogenous Antimicrobial Peptides That Enhance Porcine Healthmentioning
confidence: 99%
See 1 more Smart Citation